Perlindungan Hukum Terhadap Karyawan Notaris yang Menjadi Saksi Akta Autentik - Ida Bagus Gede Widyana Putra; I Nyoman Putu Budiartha; Anak Agung Istri Agung (Warmadewa Press, 2025)
Article 15 paragraph (1) of the UUJN explains that notaries are authorized to make authentic deeds and other documents. For a notary, having employees is a necessity. In the midst of the process of making acutely talk deeds, a Notary cannot do everything by himself, especially for administrative matters. and to help with administrative matters, Notary Employees are also required to serve as witnesses in the legalization of the deeds made. However, the extent of the responsibility of notarial employees who serve as instrumental witnesses in the execution of authentic deeds and in the course of the execution of notarial deeds is not clear as well as the extent of notarial employees who are legally protected as instrumental witnesses of authentic deeds executed before notaries. This study uses normative legal analysis. The results found are that notary employees who have the role of instrumental witnesses are protected by law and included in the flexibility outside of Law of the Republic of Indonesia No. 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning the Position of Notary, namely Law No. 31 of 2014 concerning Amendments to Law No. 13 of 2006 concerning Witness and Victim Protection.